2009
DOI: 10.1186/1755-8794-2-24
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of human glaucomatous optic nerve head astrocytes

Abstract: Background: Astrocyte activation is a characteristic response to injury in the central nervous system, and can be either neurotoxic or neuroprotective, while the regulation of both roles remains elusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 103 publications
1
47
0
1
Order By: Relevance
“…These inflammatory processes may be either damaging or protective (52,53), and future experiments are needed to determine the roles of specific molecules. It is difficult to compare our data with previous gene expression profiling studies of human glaucoma and animal models of glaucoma, as the complete datasets are not always available, and criteria for determining DE genes can vary (22,(24)(25)(26)54). Nevertheless some similarities are evident, including changes in immune/inflammatory and ECM genes.…”
Section: Figurementioning
confidence: 57%
“…These inflammatory processes may be either damaging or protective (52,53), and future experiments are needed to determine the roles of specific molecules. It is difficult to compare our data with previous gene expression profiling studies of human glaucoma and animal models of glaucoma, as the complete datasets are not always available, and criteria for determining DE genes can vary (22,(24)(25)(26)54). Nevertheless some similarities are evident, including changes in immune/inflammatory and ECM genes.…”
Section: Figurementioning
confidence: 57%
“…Changes in astrocyte morphology, such as enlargement of the cell body and processes, as well as up-regulation of cytoskeletal and extracellular matrix proteins, have been observed in the retina and ONH in human glaucoma (Wang et al 2002;Inman and Horner 2007;Hernandez et al 2008;Kompass et al 2008;Nikolskaya et al 2009). Several studies have demonstrated that this reactivity and remodeling of astrocytes, and the increased deposition of extracellular matrix occur in early stages of experimental glaucoma (Johnson and Morrison 2009;Howell et al 2011a;Johnson et al 2011;Lye-Barthel et al 2013;Qu and Jakobs 2013).…”
Section: Activation Of Astrocytes and Microglia In The Optic Nerve Hementioning
confidence: 99%
“…2, 15, 23). These studies identified changes in multiple genes/pathways related to immune responses, as well as structural and inflammatory changes in the ONH (8,24,25). The cause and impact of most of these changes in glaucoma remain to be determined, however.…”
mentioning
confidence: 99%